Material Design Of Iii-Nitride Ternary Via First Principles Calculations - Chang, Robin Yee Hui (2017)
III-nitride semiconductors exhibit an array of exceptional features, including broad coverage of spectral frequencies range and reasonable wear resistance, making them desirable materials in a variety of engineering applications. Due to these capabilities, extensive researching works have been carried out on their binary systems over the past few decades. In the case of ternary composites, AlxGa1-xN and InxGa1-xN are comprehensively studied while the same enthusiasm cannot be said for AlxIn1-xN. Numerous experimental studies have shown that the formulation of a quality AlxIn1-xN crystal is undeniably challenging, due to mismatch of certain physical properties between its parent blocks. Herein, by applying ab initio crossbreed evolutionary computations, extensive search for the thermodynamically and practically stable composites of AlN-InN was performed. Simulations were conducted at atmospheric pressure initially, with each structure underwent several stages of optimization via density functional theory, relaxing its cell shape and internal atoms. Optimized structures were selected based on a fitness value, which is the formation enthalpy per cell (Δ